Strategic Approach to the Development of Cultural Tourism Potential in Penataran Village, Blitar Regency: Pendekatan Strategis terhadap Pengembangan Potensi Wisata Budaya Desa Penataran, Kabupaten Blitar - Novita Sari, Diah Ayu; Badriani, Ririn Endah; Revana, Dano Quinta (MATRAPOLIS: Jurnal Perencanaan Wilayah dan Kota, 2025)
Tourism activities have become an essential need for modern society living amidst the hustle and bustle of daily life. In Indonesia, the tourism sector has been designated as one of the national development priority programs. Priyanto (2016) stated that tourism has now become a growing trend within society. This trend shift is marked by a transition from conventional tourism to special interest tourism, such as culture-based tourism villages. One example is Penataran Village, which, according to Article 45 of Regional Regulation (PERDA) No. 5 of 2013 on the Spatial Plan (RTRW) of Blitar Regency, is designated as a cultural and scientific tourism area. However, Ardian (2018) highlighted that the quality of tourism development in Blitar Regency remains suboptimal. The issues include a lack of supporting infrastructure, low human resource capacity in the tourism sector, limited facilities, weak community awareness of the importance of tourism, and inadequate promotion efforts. These factors have led to stagnation in the development of several tourist destinations. This is also reflected in the Strategic Plan (RENSTRA) of the Blitar Regency Office of Tourism, Culture, Youth, and Sports for the years 2016–2021, which states that efforts in cultural preservation and development have yet to be fully optimized. This research is intended to identify the components and characteristics of cultural tourism in Penataran Village, as well as to formulate development strategies suited to the existing conditions. A qualitative data analysis approach is used to identify tourism characteristics, while the SWOT analysis method is applied to formulate development strategies. The research findings resulted in four key strategies: (1) Utilizing tourism potential through government-initiated programs to attract visitors; (2) Providing accommodation areas and souvenir centers near the tourist site to enhance the local economy; (3) Supervising and maintaining existing facilities; and (4) Positioning Penataran’s cultural tourism area as an educational destination offering historical and cultural values.